How 'the System' Affects job Satisfaction and Intention to Stay or Leave—A Qualitative Study Among Child Welfare and Protection Workers in Norway. - Nilsen, Kristel Høie; Lauritzen, Camilla; Vis, Svein Arild; Iversen, Anita (Child & Family Social Work, 2026)
This article presents the findings of a study examining the factors that influence the intentions of Norwegian child welfare and protection workers to either remain in or leave their positions. It explores the elements that sustain their motivation and commitment, as well as those that contribute to their sense of challenge during difficult times. The study involved group interviews with 11 experienced workers, all of whom expressed a profound, idealistic passion for child welfare and protection as the primary driver for their continued engagement in a demanding and intricate field. Concurrently, they voiced their frustration with systemic inefficiencies that obstruct their ability to perform their duties effectively. The study highlights the significance of effective leadership and collegial support as key factors that help these professionals cope with the challenges posed by an underperforming system.